2019
DOI: 10.6007/ijarbss/v9-i6/6041
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Determinants of Patient Satisfaction: A Study in a Turkish Context

Abstract: Patient satisfaction is at the heart of all health care activities; and thus, it requires a special attention. Among various approaches to patient satisfaction, those using patients' demographics have very mixed results. An attempt for clarification is needed. For this reason, this study aims to scrutinize possible effects of patients' demographic features on their satisfaction. Data were collected from 372 participants who actively received health services from the clinics of eight private and public general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…The results of this study are in line with research (Ayranci & Atalay, 2019) especially those relating to adequate parking lots and sufficient lighting. The results of this study also support the results of previous studies by (Javed et al, 2019) that the facilities has a significant effect on patient satisfaction, especially for private hospitals not owned by the government because based on consideration of costs that are more affordable for patients whereas if for private hospitals owned by patients can't afford to pay.…”
Section: H6: There Is An Influence Between the Facilities On Patient supporting
confidence: 86%
See 3 more Smart Citations
“…The results of this study are in line with research (Ayranci & Atalay, 2019) especially those relating to adequate parking lots and sufficient lighting. The results of this study also support the results of previous studies by (Javed et al, 2019) that the facilities has a significant effect on patient satisfaction, especially for private hospitals not owned by the government because based on consideration of costs that are more affordable for patients whereas if for private hospitals owned by patients can't afford to pay.…”
Section: H6: There Is An Influence Between the Facilities On Patient supporting
confidence: 86%
“…Patient satisfaction is a major concern in providing health services in order to improve the International Journal of Human Resource Studies ISSN 2162-3058 2020 quality and effectiveness of services (Ayranci & Atalay, 2019). Patient satisfaction is also a major concern and priority in the health system.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found different results, i.e. married patients were more satisfied with health services than single patients, divorced or patients living with partners (Ayranci & Atalay, 2019). Edmealem et al (2019) also found that married patients were more satisfied with nursing care than single patients were.…”
Section: Differences In Patient Satisfaction Levels Based On Marital mentioning
confidence: 99%